Secant Condition Free of a Spectral PRP Conjugate Gradient Method - bbas Yakubu, Usman A; Mamat, Mustafa; Afendee Mohamed, Mohamad; ., Sukono; Rivaie, Mohd (International Journal of Engineering and Technology, 2018)
Recently conjugate gradient method have been in practice widely to solve unconstrained minimization problems as a result of fewer storage locations and less computational expensive in dealing with the large-scale problems. In this work, we suggested a spectral PRP CG method without employing the secant condition and use some unconstrained problems with many variables to prove its sufficient descent as well as global convergence, the results is validated by apply exact line search.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â